An Inexpensive Method for Evaluating the Localization Performance of a Mobile Robot Navigation System - Kikkeri, Harsha; Parent, Gershon; Jalobeanu, Mihai; Birchfield, Stan (IEEE International Conference on Robotics and Automation (ICRA), 2014)
We propose a method for evaluating the localization accuracy of an indoor navigation system in arbitrarily large environments. Instead of using externally mounted sensors, as required by most ground-truth systems, our approach involves mounting only landmarks consisting of distinct patterns printed on inexpensive foam boards. A pose estimation algorithm computes the pose of the robot with respect to the landmark using the image obtained by an on-board camera. We demonstrate that such an approach is capable of providing accurate metric estimates of a mobile robot's position and orientation with respect to the landmarks in arbitrarily-sized environments over arbitrarily-long trials. Furthermore, because the approach involves minimal outfitting of the environment, we show that only a small amount of setup time is needed to apply the method to a new environment. Experiments involving a state-of-the-art navigation system demonstrate the ability of the method to facilitate accurate localization measurements over arbitrarily long periods of time.